2011
DOI: 10.1021/ja2095602
|View full text |Cite
|
Sign up to set email alerts
|

Degradability of Poly(Lactic Acid)-Containing Nanoparticles: Enzymatic Access through a Cross-Linked Shell Barrier

Abstract: Comparative studies of bulk samples of hydrolytically-degradable poly(lactic acid) (PLA) vs. core-shell block copolymer micelles having PLA cores revealed remarkable acceleration in the proteinase K enzymatic hydrolysis of the nanoparticulate forms, and demonstrated that even with amidation-based shell crosslinking, the core domain remained accessible. Kinetic analyses by 1H NMR spectroscopy showed less than 20% lactic acid released from enzymatically- catalyzed hydrolysis of poly(L-lactic acid) in bulk, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 49 publications
1
103
0
Order By: Relevance
“…Our data show that dC 3 and dC 6 prodrugs were readily converted to β-lap inside the micelles by PLE [42], however, the dC 6 micelles had slower release kinetics of β-lap from micelles than dC 3 micelles (Fig. 3a).…”
Section: Discussionmentioning
confidence: 87%
“…Our data show that dC 3 and dC 6 prodrugs were readily converted to β-lap inside the micelles by PLE [42], however, the dC 6 micelles had slower release kinetics of β-lap from micelles than dC 3 micelles (Fig. 3a).…”
Section: Discussionmentioning
confidence: 87%
“…However, proteinase K can still access to the intra-spherulite amorphous phase and hydrolyse the spherulitic superstructure. It has been shown that it can even degrade a core of polylactide trapped in a crosslinked shell [42]. The SEM pictures of the sample surfaces after enzymatic degradation are shown in Fig.…”
Section: Pla Crystallization Kineticsmentioning
confidence: 99%
“…[15] This core-based enzyme prodrug conversion also agrees with studies by Wooley et al, who reported the hydrolysis of micelle cores by proteinase K in crosslinked micelles. [16] …”
mentioning
confidence: 99%